The influence of the medieval monuments of the criminal law of Belarus and Germany on the differentiation of punishment in modern legislation - Shidlovsky, Andrei V. (Journal of the Belarusian State University. Law, 2019)
It is proved that the norms of historical monuments of the criminal law of Belarus and Germany in the late Middle Ages form the basis for the differentiation of punishment in modern legislation. The history of system-forming factors of the formation of criminal sanctions for crimes is investigated. Legal approaches to the use of punishments in the form of deprivation of liberty and the death penalty are analyzed. The conclusion is made about the historical and legal transfer of the main types of punishment from Roman, medieval Belarusian and Ger man criminal law into modern national criminal legislation. The general features and legislative traditions of modern Belarusian and German criminal law are generalized due to the influence of fundamental historical monuments of the XV–XVI centuries. Differences in approaches to the establishment of differentiation of punishment and criminal responsibility, taking into account the peculiarities of national law formation and the established law enforcement practice under the current Criminal Code of the Republic of Belarus and the Criminal Code of the Federal Republic of Germany, are revealed.
Keywords: punishment; system of punishments; differentiation of punishment; guilt; the severity of the offense; the death penalty; imprisonment; the GDL Statutes; «Carolina»